MANFAAT MASSASE SIMPISIS PUBIS DAN PENGENCANGAN MUSCULUS TRANSVERSUS ABDOMINIS TERHADAP PERCEPATAN PENGELUARAN URIN PADA IBU POST PARTUM SPONTAN - Lestari, Uti (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
ABSTRACT: at the time of parturition occurring physiological and psychological changes that cause discomfort during childbirth are often encountered one of them namely urinal system changes include urinary tract infections, urinary incontinence, or urine retensio. Massase simpisis pubis with techniques can help relaxation through blood flow in the affected areas, stimulating the receptor-receptor raba skin so merilaksasikan feeling comfortable so that it does not occur in the production of URurin.dan trauma intrapartum happens because the emphasis is the head of the fetus on pelvic floor resulting in pelvic floor muscles become weak, can be repaired by tightening technique musculus abdominis transverse foramen. To find out the benefits of massase simpisis pubis and tightening of the musculus abdominis transverse foramen against the acceleration of spending on urine in the mother post!, spontaneous. Experimental research design with Cross Sectional. The subject in this study population consisted of a number of postpartum mothers 115 spontaneous and sample of 60 mothers postpartum spontaneous. Data shape ratio using the formula t-independent test test in SPSS software program. Based on the results of the analysis of data obtained the value t calculate 2.81011. If df = 60-2 = 58 and Î± (5%) then the obtained t table 2.045. It turns out t calculate > t table (2.81011 > 2.001717), meaning Ho denied and Ha is received. This means that there are massase benefits simpisis pubis and tightening of the musculus abdominis transverse foramen against the acceleration of spending on urine in the mother post spontaneous. There are benefits massase simpisis pubis and tightening of the musculus abdominis transverse foramen against the acceleration of spending on urine in the mother post!, spontaneous. Â Keywords: Massase Simpisis Pubis and tightening of the Musculus Abdoministransverse foramen, expenses of urine post